PENERAPAN MODEL PEMBELAJARAN TPS DALAM PENINGKATAN HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI KELAS XI IPS SMA NEGERI 1 SINUNUKAN - Ramlan Sihotang (Jurnal Guru Kita PGSD, 2017)
Abstract : Application of TPS Learning Model in Improving Student Learning Outcomes in Economics Subjects Class XI IPS SMA Negeri 1 Sinunukan. This study aims to improve students' understanding, improve student learning outcomes and student learning activities. Subjects in this study as many as 27 people. The results of the study were: Student activity data on Cycle I, among others: writing / reading (38%), working (34%), asking fellow friends (7%), asked teachers (11%), and irrelevant to KBM (10%). And the student activity data on Cycle II are: writing / reading (45,6%), work (33,8%), asking fellow friend (7.5%), ask teacher (7.5%), relevant to KBM (5.6%). Student learning outcomes in Formative I and Formative II showed 16 students were completed individually, while the class was not complete. In Cycle II, 25 students were completed individually, while the class was completed with the average of cycle I and cycle II are 75 and 80 and the percentage of classical completeness is 57.1% in cycle I and 89.2% in cycle II. Keywords : TPS Learning Model, Learning Outcomes, Learning Activity Abstrak : Penerapan Model Pembelajaran TPS Dalam Peningkatan Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi Di Kelas XI IPS SMA Negeri 1 Sinunukan. Penelitian ini bertujuan untuk meningkatkan pemahaman siswa meningkatkan hasil belajar, serta aktivitas belajar siswa. Subjek penelitian berjumlah 27 orang. Adapun hasil penelitian yakni : Data aktivitas siswa pada Siklus I antara lain: menulis/membaca (38%), bekerja (34% ), bertanya sesama teman (7%), bertanya kepada guru (11%), dan yang tidak relevan dengan KBM (10%). Dan Data aktivitas siswa pada Siklus II yaitu : menulis/membaca (45,6%), bekerja (33,8%), bertanya sesama teman (7,5%), bertanya kepada guru (7,5%), dan yang tidak relevan dengan KBM (5,6%). Hasil belajar siswa pada Formatif I dan Formatif II menunjukkan 16 orang siswa tuntas secara individu, sedangkan kelas tidak tuntas. Pada Siklus II, tuntas secara individu sebanyak 25 orang siswa, sedangkan kelas adalah tuntas dengan rata-rata siklus I dan siklus II adalah 75 dan 80 dan persentase ketuntasan klasikal adalah 57,1% pada siklus I dan 89,2% pada siklus II. Kata Kunci : Model Pembelajaran TPS, Hasil Belajar, Aktivitas Belajar